Impact of CO2 concentration and ambient conditions on microalgal growth and nutrient removal from wastewater by a photobioreactor - Almomani, Fares; Al Ketife, Ahmed M. D.; Judd, Simon J.; Shurair, Mohamed; Bhosale, Rahul R.; Znad, Hussein; Tawalbeh, Muhammad (Elsevier, 2019)
The increase in atmospheric CO2 concentration and the release of nutrients from wastewater treatment plants (WWTPs) are environmental issues linked to several impacts on ecosystems. Numerous technologies have been employed to resolves these issues, nonetheless, the cost and sustainability are still a concern. Recently, the use of microalgae appears as a cost-effective and sustainable solution because they can effectively uptake CO2 and nutrients resulting in biomass production that can be processed into valuable products. In this study single (Spirulina platensis (SP.PL) and mixed indigenous microalgae (MIMA) strains were employed, over a 20-month period, for simultaneous removal of CO2 from flue gases and nutrient from wastewater under ambient conditions of solar irradiation and temperature. The study was performed at a pilot scale photo-bioreactor and the effect of feed CO2 gas concentration in the range (2.5–20%) on microalgae growth and biomass production, carbon dioxide bio-fixation rate, and the removal of nutrients and organic matters from wastewater was assessed. The MIMA culture performed significantly better than the monoculture, especially with respect to growth and CO2 bio-fixation, during the mild season; against this, the performance was comparable during the hot season. Optimum performance was observed at 10% CO2 feed gas concentration, though MIMA was more temperature and CO2 concentration sensitive. MIMA also provided greater removal of COD and nutrients (~83% and >99%) than SP.PL under all conditions studied. The high biomass productivities and carbon bio-fixation rates (0.796–0.950 gdw·L−1·d−1 and 0.542–1.075 gC·L−1·d−1 contribute to the economic sustainability of microalgae as CO2 removal process. Consideration of operational energy revealed that there is a significant energy benefit from cooling to sustain the highest productivities on the basis of operating energy alone, particularly if the indigenous culture is used.
Keywords: Nutrient removal; Growth rate; Biomass production; Carbon capture; Energy balance